An Analysis on Adoption of Alternative Rites of Passage for Girls in Elgeiyo/Marakwet County, Kenya - Kipkorir, Daniel; Kareithi, Joram; Wandere, Donald; Kamara, Eunice (Advances in Social Sciences Research Journal, 2018)
Alternative rites of passage are modern cultural practices developed more than two decades ago to substitute the harmful tradition of female circumcision in many parts of Africa. Designed for girls aged 10-16, the model entails teaching teenagers marital skills, physical dangers of female cut, healthcare and prevention of sexually transmitted infections including HIV/AIDS. We carried out a study in 2015 in the Endo Ward of Elgeiyo/Marakwet County, Kenya, to appraise adoption of alternative rite of passage for girls in the region. The Endo Ward is a rural area predominantly inhabited by the Marakwet, a sub-group of Kalenjin speaking people which comprise the Kipsigis, Nandi, Tugen, Keiyo, Pokot and Sabaot. The region was purposely sampled for the study because it is one of the areas that often records high prevalence of circumcision of girls in Kenya. Twenty in-depth interviews, 10 with elderly men and 10 with elderly women, were conducted. The study also employed 10 units of focus group discussion and 16 key informant interviews with alternative rite of passage “teachers”, opinion and religious leaders, Non-governmental and community based organizations managers and a medical practitioner. Qualitative data were translated, transcribed, coded, and subjected to thematic analysis and presented in narrative and verbatim form. The study suggests that the Marakwet people of Endo Ward are slow in the uptake of alternative rite meaning that circumcision of girls could continue for long period before it is eradicated. For more adoption of the model, the study recommends more involvement of Marakwet women in the teaching of Marakwet traditional values, adequate support of Marakwet girls who denounce the tradition and a review of the alternative rite of passage programme so as to provide sufficient training on gender roles, and symbolic elements of the community.